1991
DOI: 10.2307/1966477
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sexuality and Fertility in Kenya: A Survey of Knowledge, Perceptions, and Practices

Abstract: This article presents findings from a survey conducted in Kenya in 1985 of the reproductive health knowledge, attitudes, and practices among more than 3,000 unmarried Kenyan youth, students and nonstudents, between the ages of 12 and 19. The survey was designed to elicit information that would be useful in gauging the kinds of problems Kenyan adolescents face in order to design programs that meet their needs. The study shows that although a solid majority of adolescents appear to have received information on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 4 publications
2
34
2
Order By: Relevance
“…However, throughout the process of data collection, it became clear that the lack of information about their sexuality and reproductive system was a major determinant of unplanned pregnancies, especially for 13-year-olds and those who became pregnant soon after their first intercourse. Dialogues about sex and contraception are inexistent within the family domain, and the formal knowledge acquired at school doubtfully covers all their queries 20,22,23,35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, throughout the process of data collection, it became clear that the lack of information about their sexuality and reproductive system was a major determinant of unplanned pregnancies, especially for 13-year-olds and those who became pregnant soon after their first intercourse. Dialogues about sex and contraception are inexistent within the family domain, and the formal knowledge acquired at school doubtfully covers all their queries 20,22,23,35 .…”
Section: Discussionmentioning
confidence: 99%
“…This was true for most girls who got pregnant very early, showing insufficient or inadequate knowledge on the matter, including formal knowledge gained at school 20,22,23 .…”
Section: Knowledge and Attitudes Towards Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It could then be confirmed that there is a great unmet need for services, but awareness and psychological access are essential. Several studies in Africa have reported difficulty in obtaining contraception, infrequent or unplanned sexual activity, opposition from partner and religious proscription 2,4,12 as the main reasons for low adoption of contraceptive usage. The above indices of adolescents' health status in Nigerian states have suggested the need for individuals to accord adolescents the universal right to sexual and reproductive health, in order to reduce the risks of teenage pregnancies, STDs and HIV/ AIDS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even where the law permits abortion, adolescents are more likely than their adult counterparts to delay or avoid accessing safe abortion services due to ignorance about pregnancy or availability of safe, legal services, and above all, the desire to conceal the pregnancy from the family and continue with school, and lack of means or capacity to afford, on their own, the cost of safe abortion services. 48 Lack of youth-friendly sexual and reproductive healthcare services, and uncertainty among providers whether minors can legally access abortion services without the involvement of their parents serve as additional barriers to access. 49 Amongst all regions, the SubSaharan region has the highest proportion of women aged 15-19 years who have recourse to unsafe abortion.…”
mentioning
confidence: 99%